2019
DOI: 10.1021/acs.jafc.8b07166
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant and Anti-Inflammatory Activities of Buffalo Milk δ-Valerobetaine

Abstract: δ-Valerobetaine (δVB), a constitutive metabolite of ruminant milk, is produced in the rumen from free dietary Nε- trimethyllysine occurring ubiquitously in vegetable kingdom. The biological role of δVB is poorly known. Here, the antioxidant and anti-inflammatory potential of buffalo milk δVB was tested in vitro during high-glucose (HG)-induced endothelial damage. Results indicated that δVB (0.5 mM) ameliorated the HG cytotoxicity (0.57 ± 0.02 vs 0.41 ± 0.018 O.D. (P < 0.01). Interestingly, buffalo milk extract… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
47
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 32 publications
(50 citation statements)
references
References 45 publications
1
47
0
2
Order By: Relevance
“…It is tempting to speculate that pure betaines cause an increased metabolic oxidative burden which might directly/indirectly affect nuclear expression of SIRT1. Nevertheless, it is evident that milk, even at µM concentration of betaines, displays a more robust effect on SIRT1 and cell proliferation compared to single tested betaines (mM), probably due to the occurrence of other known bioactive molecules, including short-chain acylcarnitines and small peptides [6,9].…”
Section: Discussionmentioning
confidence: 95%
See 3 more Smart Citations
“…It is tempting to speculate that pure betaines cause an increased metabolic oxidative burden which might directly/indirectly affect nuclear expression of SIRT1. Nevertheless, it is evident that milk, even at µM concentration of betaines, displays a more robust effect on SIRT1 and cell proliferation compared to single tested betaines (mM), probably due to the occurrence of other known bioactive molecules, including short-chain acylcarnitines and small peptides [6,9].…”
Section: Discussionmentioning
confidence: 95%
“…A growing body of evidence shows that betaines are important human nutrients that participate in the methionine cycle acting as methyl donors. Compounds belonging to this class, such as glycine betaine, stachydrine, ergothioneine, γ-butyrobetaine (γBB), and δ-valerobetaine (δVB) show protective effects against cardiovascular disease and cancer [3][4][5][6][7][8].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Among the two putatively identified metabolites, glycine betaine is of particular interest. Glycine betaine is a methyl group donor that functions in the normal metabolic cycle of methionine-transforming the harmful homocysteine into methionine [31]-modulates cellular responses to osmotic stress [32], acts as an osmolyte and cryoprotectant [33] and exerts antioxidant and anti-inflammatory actions [34,35]. It has been reported that betaine improves the quality of cryopreserved spermatozoa in ram [36,37] and stallions [38,39].…”
Section: Metabolomic Analysis Of Spermatozoa Before and After Cryoprementioning
confidence: 99%